Analisis Perubahan Indeks Harga Saham Gabungan dan Harga Saham Perusahaan BUMN Konstruksi Tahun 2020-2022 di Pasar Modal Indonesia - Tuasikal, Moh. Irfan; Susianti, Susianti (Jurnal Paradigma Ekonomika, 2022)
Investment is an activity to invest a certain amount of funds at present time to gain profits from the future. This makes investors need to consider carefully so that their investment objectives can be achieved. The Covid 19 incident has put the Composite Stock Price Index on the Indonesian Capital market under pressure. This situation also affected the share prices of state-owned construction companies, such as WIKA, PTPP, ADHI and WSKT. The method used in this study is to look at changes in the JCI that have occurred in the capital market, their effect on the stock prices studied, and by looking at the financial performance of the state-owned construction companies under study. Furthermore, from the studies that have been carried out, the results can be used as a consideration in selecting shares of the state-owned construction company that are suitable as investment targets. The results show that during the period of observation on the Indonesian Stock Exchange there was an increase in the JCI, which also affected the share prices of state-owned construction companies